The Influence of Instagram Stories on Career Paths of Female Journalism Graduates of Multimedia University of Kenya - Kwamboka, Omambia Joan; Kigatiira, Kinya; Wagumba, Collins (International Journal of Research in Interdisciplinary Studies, 2024)
This research analyzed the influence of Instagram stories on the career path of female journalism graduates of the Multimedia University of Kenya. The study objective was to determine the influence of Instagram stories on the career path of female graduates of Multimedia University of Kenya. The research was guided by the Cultivation Theory and the Uses and Gratifications Theory, and a thorough review of relevant literature provided a solid foundation for the study. Data collection tools included content analysis and interviews. The study comprised of 15 participants. The thematic analysis approach identified the patterns, themes and meanings in the data collected from the Instagram stories using the content analysis process. The study revealed the intricate relationship between the Instagram platform and female journalism graduates from the Multimedia University of Kenya and Instagram. The platform, through its diverse features, emerges as a powerful influencer in shaping career paths. Respondents indicated that Instagram stories have helped them like their careers more because they interact daily with people who are already pursuing their careers. This has made them work even harder to get to where their mentors are. This research recommends recognizing the significance of Instagram influencers in shaping career perceptions and establishing mentorship programs that connect female journalism graduates with successful influencers. The mentorship programs emphasize transparency and realism in portraying career paths. Through these connections, graduates will gain a more accurate understanding of diverse career journeys within journalism and receive support in navigating the challenges and opportunities presented by the field.